Effects of Ga substitution on electronic and thermoelectric properties of gapless semiconductor V3Al. Issue 7 (29th January 2019) - Chen, Xiaorui; Huang, Yuhong; Liu, Jing; Yuan, Hongkuan; Chen, Hong
Abstract : Reduced thermal conductivity and enhanced thermoelectric efficiency was demonstrated by Ga substitution for Al at room temperature in p-type V3 Al1− x Ga x . Abstract : Thermoelectric properties of the antiferromagnetic (AF) gapless semiconductor (GS) V3 Al were optimized by substituting Al with the isoelectric element Ga in the D03 structure. Structural and mechanical stability, electronic structure and transport properties of V3 Al1− x Ga x ( x = 0.25, 0.5, 0.75 and 1) compounds have been studied based on first-principles calculations with the combination of the semi-classical Boltzmann theory and deformation potential theory. All the compounds are structurally and mechanically stable gapless semiconductors. The Ga substitution for Al leads to an appreciably decreased thermal conductivity and an undesirable decrease in power factor, but contributes more to the decreased thermal conductivity. Consequently, the figure of merit ( zT ) is effectively improved in V3 Al0.75 Ga0.25 and V3 Ga compounds with respect to V3 Al.